2023
DOI: 10.2147/ijgm.s404418
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of Sharps Injuries Incidence Amongst Healthcare Workers in the United States

Abstract: Reporting sharps injuries is crucial for healthcare worker occupational safety. However, these incidents are often underreported, thus posing potentially dangerous working environments. Previous small and limited studies have quantified this underreporting in specific groups of healthcare workers. This study aims to expand on these studies by further quantifying sharps injury incidences through a national study, thus better understanding healthcare reporting behaviors and the reasons for underreporting. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the perioperative setting, the prevalence of needlestick and sharps injuries among medical students and surgical residents who are beginning their clinical experiences has been significant. [5][6][7] In 2020, researchers surveyed 138 surgical residents at one US hospital and found that 68 (49%) had experienced at least one needlestick or sharps injury; the reporting rates for the injuries ranged from 64% for orthopedic surgery residents to 100% for urology and oral-maxillofacial surgery residents. 5 When responding to a question on why they did not report needlestick and sharps injuries, the most common reasons were associated with the amount of nonpatient-care time required for paperwork completion and injury evaluation and treatment.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In the perioperative setting, the prevalence of needlestick and sharps injuries among medical students and surgical residents who are beginning their clinical experiences has been significant. [5][6][7] In 2020, researchers surveyed 138 surgical residents at one US hospital and found that 68 (49%) had experienced at least one needlestick or sharps injury; the reporting rates for the injuries ranged from 64% for orthopedic surgery residents to 100% for urology and oral-maxillofacial surgery residents. 5 When responding to a question on why they did not report needlestick and sharps injuries, the most common reasons were associated with the amount of nonpatient-care time required for paperwork completion and injury evaluation and treatment.…”
mentioning
confidence: 99%
“…5 Medical students and residents are more vulnerable to sharps injuries and are less likely than nurses to report such injuries. 6 Dedicated sharps injuryprevention education sessions that address the need for expedited reporting and treatment and streamlined reporting processes for needlestick and sharps injuries may encourage consistent reporting and lead to improved workplace safety. 5 Some researchers suggest that educational interventions regarding sharps safety can reduce the incidence of sharps injury and increase reporting of injuries; [7][8][9] however, results of a Cochrane systematic review with meta-analysis show that these improvements tend to be small and short-lived.…”
mentioning
confidence: 99%
See 2 more Smart Citations